Postnatal Morphological Development of Pancreas in Guinea Pig (Caviaporcellus) - S. Rajathi; Geetha Ramesh; T. A. Kannan; K. Raja (Indian Journal of Veterinary Anatomy, 2025)
The pancreas is an accessory organ of the digestive system and also an important endocrine organ of vertebrates. The research work is carried out to study the morphological development of the pancreas in postnatal age groups of guinea pig. Guinea pigs were procured from the Department of Laboratory Animal Medicine, TANUVAS. The pancreas was white fatty coloured, irregularly lobulated and located on the left side of the abdominal cavity. It presented three lobes viz; splenic, ventricular and intestinal lobe. The main pancreatic duct was formed by the union of pancreatic ducts of all the three lobes.